Menalar Dilema Etis Dalam Film Silence - Abel Kristofel Aruan (Indonesian Journal of Theology, 2018)
Silence was a provocative film, particularly for Christians viewers. Aside from sketching stories of great interest concerning challenges endured by Jesuit missionaries to Japan, the film presents a deep ethical struggle one finds worthy of careful analysis. In the most climactic scene, the missionary Rodrigues faces an ethical dilemma. He must desecrate fumi-e, a bronze board depicting Christ Jesus, in an act of apostasy to save five tortured and dying hostages. Rodrigues must choose: apostasy or allowing people to die. In this article, the author attempts to reason through Rodrigues' ethical dilemma, without providing conclusive arguments in support of any ethical choices the author might prefer, to broaden the thinking of his readers. Following preliminary considerations for how to define the category of ethical dilemma, the author provides two key questions for evaluating solutions belonging to the moral agent. (α) Concerning competing moral demands, which one is highest in standing amid the rest? (β) Concerning available interventions by the moral agent, which action most effectively realizes the highest moral demand? These two lines of inquiry frame three proposed solutions. Finally, the author also proposes a fourth solution termed Kierkegaardian conflict, following the philosopher of ethics Phillip L. Quinn, whose own proposal, too, remains inconclusive for resolving the dilemma.